Dilemma of applying Islamic sharia’a through takhayur and talfiq principles in the modern Egyptian legal system - Ahmed, Aly Abdulrahman (AUC Knowledge Fountain, 2016)
For many Egyptians, the only path to modernity in the Egyptian legal system is believed to be through utilizing Islamic sharia’a. Between the nineteenth and twentieth centuries, the Egyptian legal elite worked to introduce a modern interpretation and application of Islamic sharia’a. The Islamic principles takhayur and talfiq were used to do this. While the main usage of takhayur and talfiq was to legitimize the modern legal system by maintaining the usage of Islamic sharia’a, the legal practice reached a contradictory outcome. The Courts have been unable to decide on the exact relationship between Islamic sharia’a and other legal texts. This confusion has produced ambiguity and uncertainty in legal practice. This situation of uncertainty in the legal system is inevitable because of the differences in the underlying nature and philosophy of the modern and sharia’a legal systems. Accordingly, the Egyptian legal system may require additional secular reform to reduce the uncertainty by stressing the superiority of the legal text.